Non-surgical treatments for Morton's neuroma: A systematic review. Issue 7 (October 2020) - Thomson, Lauren; Aujla, Randeep S.; Divall, Pip; Bhatia, Maneesh
Highlights: Corticosteroid remains the mainstay of treatment with excellent or good satisfaction overall. Alcohol injection shows early promise there were recurrent issues with post injection pain and subsequent surgical excision. Radiofrequency and cryoablation showed some improvement would benefit from larger trials. There is minimal evidence for the use of shockwave therapy, botulinum toxin, YAG-Laser or Capsaicin therapy. There is no evidence to support the use of a pronation or supination orthosis. Injections for Morton's Neuroma can be successfully performed without ultrasound guidance using landmark techniques. Abstract: Title: Non-surgical treatment for Morton's neuroma: a systematic review. Background: Morton's neuroma (MN) is an entrapment degenerative neuropathy with a strong predilection for the 3rd interdigital web space. The objective of our study was to identify the most significant evidence produced for the non-operative treatment of Morton's neuroma and assess outcomes of these interventions. Method: The electronic databases Medline, Ovid EMBASE, CINAHL and Cochrane CENTRAL from inception to October 2018 were searched. Two independent reviewers assessed the quality of the studies using the Modified Coleman Criteria. Statistics were combined across cohort studies to calculate pooled mean results, and improvements in outcomes. Results: Initial electronic and hand search identified 486 studies. After title and abstract review there were 38 that went on to full-text review. Finally, 22 studies were included in the final review. We identified 9 different non-operative treatment modalities; Corticosteroid injection, Alcohol injection, Extra-corporeal Shockwave therapy (ESWT), Radiofrequency Ablation (RFA), Cryoablation, Capsaicin injection, Botulinum toxin, Orthosis and YAG Laser Therapy. Corticosteroid showed a statistically significant reduction in mean VAS over all their studies (p < 0.01), with 50% success at 12 months. Alcohol showed promising short-term pain-relieving results only. Orthotics, Capsaicin injections, Cryoablation, Botulinum toxin, RFA and ESWT did show statistically significant improvements, but with limitation to their application. Conclusion: Following review, the authors would recommend the use of corticosteroid injections to treat Morton's neuromas. The authors feel that radio-frequency ablation and cryoablation would benefit from further well designed randomised controlled trials.